Social networks as a tool for job search - Lorincová, Silvia; Ližbetinová, Lenka; Brodský, Zdeněk (Univerzita Pardubice, 2018)
The information technology has caused an absolute revolution. Therefore, searching job through social networks is highlighted as it is perspective way how to find a job. At the global level, social networks are used by more than 90% of companies in process of recruitment. Nowadays, social networks are beginning to be applied by Czech and Slovak companies as well. The objective of the research is to identify the differences in the using of social networks in job search in Czech and Slovak Republic. Findings indicate that, only 2% of Czech respondents preferred social networks as a significant way of finding a job. Following the results, social networks were identified less credible by Slovak respondents, but on the other hand more then 4% of Slovak respondents preferred social networks as a toll for job search. Despite the fact that the employees in the Czech Republic and Slovakia do not really use social networks to find employment, this situation can change as respondents express the opinion acoording which social networks have potential for the future. If social networks are used more by employers as well as by potential candidates, both parties will be satisfied.
Keywords: HRM; seeking employment; recruitment; head hunting; social networks; J20; O15